A Mixed Methods Analysis of the Implementation and Uptake of the Human Papillomavirus Vaccination of Adolescent Girls in Lusaka, Zambia - Lubeya, Mwansa Ketty (University of the Witwatersrand, Johannesburg, 2024)
Background and rationale: Cervical cancer is the most common female cancer in sub- Saharan Africa compounded by the high prevalence of HIV among women of reproductive age. The human papillomavirus (HPV), mainly transmitted sexually, and persistent infection with oncogenic strains is a necessary cause of cervical cancer. The HPVs largely cause mild and self-limiting disease in those who are immunocompetent. In 2006, the World Health Organisation (WHO) approved the use of highly effective and immunogenic HPV vaccines for prepubertal girls aged 9 to 14 years, naive to sexual intercourse. Further, in 2020 WHO launched the global call for cervical cancer elimination which includes vaccinating 90% of girls by age 15 by 2023. These policies focus on improving cervical cancer primary prevention. Despite the known vaccine effectiveness and policy pronouncements, uptake remains low in many LMICS including Zambia, where there is a cervical cancer highly prevalent. The low HPV vaccine uptake is partly due to low levels of knowledge about HPV and HPV vaccines, myths and misconceptions, and vaccine mistrust. Implementation barriers, such as low adoption, human resource constraints, and coordination, hinder the successful implementation of the HPV vaccination. Zambia shares a high burden of cervical cancer, yet HPV vaccine uptake is low. The demonstration project conducted between 2013-2017 reported suboptimal coverage. Additional health facility data for 2021 and 2022 after national rollout of the vaccination reported uptake of only 30% among 14-year-old eligible adolescent girls. Factors leading to this low uptake and implementation determinants are not very well understood in the Zambian context. Therefore, this PhD aimed to understand factors associated with the uptake and implementation of the HPV vaccination of adolescent girls in Lusaka and select and tailor strategies based on their acceptability and feasibility to mitigate identified barriers. viii Methodology: This research was embedded in behavioural and implementation research with multiple stakeholders. Based on existing literature, the social-ecological model (SEM) was used to develop the conceptual framework to ensure the study was deeply grounded in theory. The health belief model (HBM) and consolidated framework for implementation research (CFIR) were used to explore participants' behavioural and implementation dimensions, respectively, at the different levels of the SEM. A mixed methods approach was employed, incorporating semi-structured interviews with adolescents, parents, teachers, and healthcare workers and a cross-sectional survey of parents. Thematic analysis and descriptive statistics were used to analyse the data, guided by the CFIR and the HBM. The nominal group technique (NGT) was used to achieve stakeholder consensus on feasible and acceptable implementation strategies to increase HPV vaccine uptake. Secondly, a scoping review was conducted following an a priori protocol to understand the implementation strategies used to increase HPV vaccination of adolescent girls in the broader context of SSA. To have clear and replicable definitions, all the identified implementation strategies were coded according to the Expert Recommendation for Implementation Change (ERIC) taxonomy, grouped into clusters, and recorded their perceived feasibility and importance. Results: This PhD identified low awareness and misinformation as significant barriers to vaccine uptake among adolescents and parents. Cultural beliefs, fears about infertility, and logistical challenges within the healthcare system were substantial obstacles. Teachers and healthcare workers pointed to inadequate training and resources as crucial limitations in program implementation. Frequently used implementation strategies in SSA from the scoping review included building a coalition, changing service sites, distributing educational materials, conducting educational meetings, developing educational materials, using mass media, involving patients/relatives and families, promoting network weaving, staging implementation scale- ix up, accessing new funding, promoting adaptability, and tailoring strategies. According to expert consensus, most of the identified implementation strategies were multifaceted and of high importance and feasibility. Conclusion: The PhD highlights the need for targeted health education campaigns, access to clear information, improved coordination between stakeholders, and the development of flexible delivery models to reach out-of-school girls. Future research should evaluate the effectiveness of the proposed strategies to assess their impact on vaccine uptake in Lusaka, Zambia and within the region.
A research report submitted in fulfillment of the requirements for the Doctor of Philosophy, in the Faculty of Health Sciences, School of Public Health, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; HPV vaccination; cervical cancer; Implementation research; SDG-3: Good health and well-being